Identification of modal parameters of non-classically damped linear structures under multi-component earthquake loading. - Mahmoudabadi, M.
A method for parametric system identification of classically damped linear system in frequency domain is adopted and extended for non-classically damped linear systems subjected up to six components of earthquake ground motions. This method is able to work in multi-input/multi-output (MIMO) case. The response of a two-degree-of-freedom model with non-classical damping, excited by one-component earthquake ground motion, is simulated and used to verify the proposed system identification method in the single-input/multi-output case. Also, the records of a 10 storey real building during the Northridge earthquake is used to verify the proposed system identification method in the MIMO case. In this case, at first, a single-input/multi-output assumption is considered for the system and modal parameters are identified, then other components of earthquake ground motions are added, respectively, and the modal parameters are identified again. This procedure is repeated until all four components of earthquake ground motions which are measured at the base level of the building are included in the identification process. The results of identification of real building show that consideration of non-classical damping and inclusion of the multi-components effect of earthquake ground motions can improve the least-squares match between the finite Fourier transforms of recorded and calculated acceleration responses.
Keywords: System identification; Modal parameters; Classical damping; Non-classical damping; Multi-component earthquake excitation; Optimal parameters